Program Intervensi Psikologis Dalam Mengatasi Perilaku Menarik Diri Dan Kesulitan Belajar Pada Siswa Sekolah Dasar - Sati Rahma; Dian Widityastuti Arini; Nindha Iqlima Meywanthi; Putri Hana Pebriana (Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to describe the implementation of a psychological intervention program in addressing withdrawn behavior and learning difficulties among elementary school students. The subjects of this study were two third-grade elementary school students who exhibited social and academic problems, including social withdrawal and disruptive behavior accompanied by learning difficulties. This research employed a qualitative case study approach using observation, interviews, and documentation. The psychological intervention program consisted of individual counseling, self-confidence training, social skills training, academic support, self-control exercises, and collaboration with teachers and parents. The evaluation results indicated positive changes in both subjects, as evidenced by increased confidence in social interactions, reduced disruptive behavior in the classroom, and improved participation in learning activities. Therefore, psychological intervention programs can be considered an effective strategy to help overcome behavioral problems and learning difficulties in elementary school students.